Variability of the mc1r gene in melanic and non-melanic Podarcis lilfordi and Podarcis pityusensis from the Balearic archipelago. - Joana M Buades (Public Library of Science (PLoS), 2013)
The association between polymorphism at the mc1r locus and colour variation was studied in two wall lizard species (Podarcis lilfordi and P. pityusensis) from the Balearic archipelago. Podarcis lilfordi comprises several deep mitochondrial lineages, the oldest of which originated in the Pliocene, while much shallower mitochondrial lineages are found in P. pityusensis. Here, we examined whether specific substitutions were associated with the melanic colouration found in islet populations of these species. Homologous nuclear sequences covering most of the mc1r gene were obtained from 73 individuals from melanic and non-melanic Podarcis from different populations (the entire gene was also sequenced in six selected individuals). MtDNA gene trees were also constructed and used as a framework to assess mc1r diversity. Mc1r showed greater polymorphism in P. lilfordi than in P. pityusensis. However, we observed no substitutions that were common to all melanic individuals across the two species. Only one significant association was detected in the mc1r partial sequence, but this was a synonymous A/G mutation with A alleles being more abundant in melanic populations. In addition, there were no associations between the main dominant phenotypes (green and brown, blue and yellow spots and ventral colour) and synonymous or non-synonymous substitutions in the mc1r gene. There was no statistical evidence of selection on mc1r. This study suggests no relationship between mc1r polymorphism and colour variation in Balearic Podarcis.